Effects of low molecular weight heparin and fondaparinux on mortality, hemorrhagic and thrombotic complications in COVID-19 patients. (May 2022) - Fragkou, Paraskevi C.; Palaiodimou, Lina; Stefanou, Maria Ioanna; Katsanos, Aristeidis H.; Lambadiari, Vaia; Paraskevis, Dimitrios; Andreadou, Elisabeth; Dimopoulou, Dimitra; Zompola, Christina; Ferentinos, Panagiotis; Vassilakopoulos, Theodoros I.; Kotanidou, Anastasia; et al.
Background: Coronavirus disease 2019 (COVID-19) is associated with increased thrombosis prevalence. However, there are insufficient data supporting the appropriate anticoagulation dose in COVID-19. Objective: We aim to systematically assess the currently available data regarding the effects of different dosing regimens of low molecular weight heparin and/or fondaparinux (LMWH/F) on mortality risk as well as the risk of arterial/venous thrombotic events and hemorrhagic complications in confirmed COVID-19 cases. Design: We conducted a living systematic review and meta-analysis on the effects of different LMWH/F doses on mortality, thrombotic and hemorrhagic events in COVID-19 patients. Data Sources and Methods: MEDLINE, Scopus, Embase, Cochrane Library, Cochrane COVID-19 study register, European Union Drug Regulating Authorities Clinical Trials Database, and ClinicalTrials.gov were searched to detect observational cohort studies and randomized-controlled clinical trials (RCTs) comparing difference doses of LMWH/F among confirmed COVID-19 cases. Results: Thirty-one eligible studies (6 RCTs and 25 cohort studies) with 11, 430 hospitalized patients were included. No association was found between LMWH/F and mortality during the following comparisons: (1) no LMWH/F versus any LMWH/F; (2) prophylactic versus higher than prophylactic LMWH/F; (3) prophylactic versus therapeutic LMWH/F; (4) intermediate versus therapeutic LMWH/F; and (5) lower than therapeutic versus therapeutic LMWH/F. Mortality was higher in patients receiving prophylactic versus intermediate LMWH/F (OR = 2.01; 95% CI: 1.19–3.39). However, this effect was mostly driven by observational data. No associations were detected between the intensity of LMWH/F and the risk of thrombotic and hemorrhagic events, except the lower risk for hemorrhage in patients on prophylactic compared to higher LMWH/F doses. Conclusion: The risk for all-cause mortality was higher in patients receiving prophylactic LMWH/F compared to those on an intermediate dose of LMWH/F, based on observational data. These results should be interpreted in light of the moderate quality and heterogeneity of the included studies. Registration: The study protocol has been registered in the International Prospective Register of Ongoing Systematic Reviews PROSPERO (Registration number: CRD42021229771).